Remineralisation Potential of Self-assembling Peptide (P11-4) Compared to Other Remineralising Agents: A Narrative Review - Dana Alsenan; Amani Rozi; Njoud Alateeq; Shog Aleban; Jana Almusallam (Journal of Clinical and Diagnostic Research, 2024)
Dental caries is a chronic infectious disease that affects the hard tissues of the teeth, primarily the enamel. Remineralisation involves depositing minerals back into demineralised enamel, repairing the damage, and preventing the formation of caries. Self-Assembling Peptide (SAP) P11-4 is a promising new remineralisation agent that mimics the natural process of remineralising dental enamel. It is a biomimetic peptide that binds to the surface of demineralised enamel, forming a three-dimensional network that supports mineral deposition and induces the production of reparative proteins. P11-4 is still in the early stages of development, but it has the potential to revolutionize the treatment of dental caries. SAP P11-4 has been shown to be safe and effective in remineralising early carious lesions. However, there is insufficient evidence to conclude that SAP P11-4 is more effective than other remineralising agents, such as fluoride, Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP), and Silver Diamine Fluoride (SDF). The present review focuses on recent studies discussing the remineralisation potential of SAP P11-4 and compares it to other available remineralising agents. Overall, the review suggests that SAP P11-4 is a promising new remineralisation agent that is effective in treating early carious lesions. However, further research is needed to compare its effectiveness to other remineralisation agents and assess its long-term efficacy.